Obstetrical and perinatal complications of mid-trimester genetic amniocentesis in twin pregnancies - Crespo Esteras, Raquel (2015)
Objectives: To determine genetic midtrimester amniocentesis outcomes in twin gestations. Design: escriptive retrospective study. Setting: Prenatal Diagnosis Unit, Hospital Universitario Miguel Servet, Instituto Aragones de Ciencias de la Salud, Zaragoza, España. Patients: Women with twin gestations. Methods: Computerized database and medical records of pregnant women attended from January 2004 to February 2008 ere reviewed. Twin pregnancies undergoing amniocentesis were compared with singleton pregnancies also exposed to amniocentesis and with unexposed twin pregnancies. Main outcome measures: Obstetrical and perinatal complications. Results: During the four years study 4 263 amniocentesis were performed, 112 in twin gestations and 4 151 in singleton gestations. Advanced maternal age and anxiety were the most common indications for amniocentesis. Fetal loss within four weeks after the procedure was 1,78% for twin pregnancies and 0,40% for singleton pregnancies. Twin gestations exposed to amniocentesis did not present other obstetrical complications or worse neonatal results. Conclusions: Based on our data and previous studies, we can advise patients undergoing mid-trimester twin amniocentesis that fetal loss rate may be slightly higher than for singleton amniocentesis. Although in hands of experienced operators amniocentesis is a safe and effective technique for prenatal diagnosis in twin gestations.